THE MAGGOT: AS A SUSTAINABLE SOLUTION OF ORGANIC WASTE MANAGEMENT AND ANIMAL FEEDING NEEDS - Yopi Harahap (Jurnal PPI Dunia, 2019)
Maggot comes from the Black Soldier Fly insect which is very active in eating a variety of organic waste. Maggot is able to process organic waste up to 52.2 kg per day. Indonesian waste dominated by organic species is 40 million tons in 2019 where 17.94% is produced by traditional markets (7 million tons). Based on BPS data, Traditional markets produce 1 ton of waste per day. By the ability of maggot to process waste, a 60 x 40 meter building is needed. Aside from being an organic waste solution but also as a producer of maggot with high protein, maggot flour and compost, it will add economic value. Organic waste production in Indonesia which continues to increase has the potential for maggot production to be continuous so that it can replace fish meal or conventional animal feed in terms of continuity. Maggot has a crude protein content of 42% so it is very good as a substitute for fish meal which is always imported. Maggot is also thought to have potential as a substitute for the MBM ration. Research shows that maggot flour can replace 75% of fish meal as an abdominal ration. The compost produced by maggot also has a greater NPK value than Em4 and cow dung, so that it has the potential to become a quality NPK fertilizer. It can be concluded maggot as an organic waste solution and potentially as a substitute for conventional sustainable feed.